2017
DOI: 10.11604/pamj.2017.27.216.11430
|View full text |Cite
|
Sign up to set email alerts
|

Performance of SD Bioline Malaria Ag Pf/Pan rapid test in the diagnosis of malaria in South-Kivu, DR Congo

Abstract: IntroductionUse of malaria rapid diagnostic tests (RDTs) has improved the management of this disease. We evaluated the validity of the SD-Bioline Malaria-Ag-Pf/Pan™ (Batch 60952) RDT supplied by the Malaria Control Program of the DRCongo.MethodscChildren (n = 460) aged below 5 years seen in curative care (CC) for suspected malaria and in pre-school consultation (PSC) in two rural centers underwent clinical evaluation and capillary blood collection for microscopic reading of thick smear (TS) and thin film (BF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
5
8
0
Order By: Relevance
“…The sensitivity of both PfHRP2 and PfPLDH RDT increased by the level of parasite density based on microscopy. This finding agrees with the WHO recommendation [31] and is in line with a number of previous studies [43,46]. This study also showed lower sensitivity for both PfHRP2 and PfPLDH in comparison with qPCR from clinical samples.…”
Section: Discussionsupporting
confidence: 93%
“…The sensitivity of both PfHRP2 and PfPLDH RDT increased by the level of parasite density based on microscopy. This finding agrees with the WHO recommendation [31] and is in line with a number of previous studies [43,46]. This study also showed lower sensitivity for both PfHRP2 and PfPLDH in comparison with qPCR from clinical samples.…”
Section: Discussionsupporting
confidence: 93%
“…MR Box assay results collected in the field at the Kakuma refugee camp had reduced overall agreement (86 and 84% for measles and rubella, respectively) with laboratory results compared to tests conducted in the laboratory. Similar observations of diminished performance in field trials relative to that determined in the laboratory have been described previously (46). There are multiple potential reasons for this effect.…”
Section: Possupporting
confidence: 84%
“…It is interesting to note that performance of some of the malaria RDTs including those evaluated in this study are comparable to using the microscope [ 7 ] despite their limitations in sensitivity and specificity [ 8 , 22 , 32 ]. One of such limitations is that some of the RDTs just as those evaluated in this study could have false positive rates >10% [ 1 , 18 , 21 ] and need to be looked at since such kits have increased possibility of giving false positive result.…”
Section: Discussionmentioning
confidence: 99%
“…The RDTs could be used for screening and diagnosis when there is the fear of reduced reliability of HRP2-detecting RDTs because of hrp2 gene deletion in some strains of malaria parasites [ 33 ]. This is on the assumption that parasites with hrp2 gene deletion are expected to produce pLDH which would be detected when the parasite is present considering the time of sample analysis [ 21 , 22 ]. However, the possibility of the RDTs being able to detect parasites with hrp2 gene deletion needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation